EVALUATION OF PLATELET AGGREGATION IN CLINICAL PRACTICE - K. B. Mirzaev; D. A. Andreev; D. A. Sychev (Столичная издательская компания, 2015)
Evaluation of platelet function with subsequent modification of antiplatelet therapy regimen is one of the areas of personalized medicine. Analysis of the causes of inadequate antiplatelet action of clopidogrel, the association of residual platelet reactivity with clinical outcomes and a review of the research on the change of antiplatelet therapy in patients with ischemic heart disease after percutaneous interventions based on the results of platelet function testing, were the aim of this review.